The Role of Corporate Governance Mechanisms in Mitigating Greenwashing Practices and Environmental Management Control Systems as a Moderating Variable in Manufacturing Companies in ASEAN - Uliani Arifah; Asniati Bahari (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Greenwashing has emerged as a critical concern in the ASEAN-5 region as stakeholder demands for environmental transparency and corporate accountability continue to intensify. This phenomenon reflects weaknesses in internal monitoring mechanisms and the integration of environmental control systems, leading some companies to provide symbolic sustainability disclosures without substantive environmental implementation. Drawing on legitimacy theory and institutional theory, this study investigates the influence of corporate governance mechanisms on greenwashing practices, examines the direct effect of Environmental Management Control Systems (EMCS) on greenwashing, and evaluates the moderating role of EMCS in the relationship between corporate governance and greenwashing among manufacturing companies in ASEAN-5 countries. This quantitative study employs secondary data obtained from manufacturing firms listed on the stock exchanges of Indonesia, Malaysia, Singapore, Thailand, and the Philippines during the 2022–2024 period. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. A two-stage approach was applied to assess the moderating effect of EMCS. The findings reveal that corporate governance mechanisms collectively have a significant negative effect on greenwashing practices. However, among the governance dimensions examined, only board environmental expertise demonstrates a significant individual impact. EMCS is found to play a direct role in reducing greenwashing practices but does not significantly moderate the relationship between corporate governance and greenwashing. These results suggest the presence of decoupling and symbolic compliance, indicating that EMCS has not yet been strategically embedded within the board’s monitoring and decision-making processes. The study highlights the importance of enhancing board ESG competencies, integrating sustainability-based executive remuneration, strengthening EMCS implementation, and improving the quality of external sustainability assurance as effective mechanisms for mitigating greenwashing practices in ASEAN manufacturing firms.